2016
DOI: 10.5713/ajas.16.0252
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sensory attributes and volatile compounds of polish dry-cured loin

Abstract: ObjectiveThe aim of this work was to determine the relationship between objective sensory descriptors and volatile flavour compound composition of Polish traditional dry-cured loin.MethodsThe volatile compounds were investigated by using solid phase microextraction (SPME) and gas chromatography–mass spectrometry (GC–MS). For sensory assessment, the quantitative descriptive analysis (QDA) method was used.ResultsA total of 50 volatile compounds were found and assigned to 17 chemical families. Most of the detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…As stated by Topel et al (2013), tenderness and solubility of the hams (among other sensory attributes such as flavor and juiciness) are also related to the intramuscular fat content. Marbling, which could be explained as visual perception of intramuscular fat content, was not significantly different between production seasons, therefore it is assumed that the fatty acid composition could have a more important role as shown by Pleadin et al (2015).Aroma and flavor are key attributes that have an impact on the overall acceptance of dry-cured products(Górska et al, 2017). Results in the present studyrevealed that butter flavor differed significantly (P<0.05) between production seasons.…”
supporting
confidence: 57%
See 2 more Smart Citations
“…As stated by Topel et al (2013), tenderness and solubility of the hams (among other sensory attributes such as flavor and juiciness) are also related to the intramuscular fat content. Marbling, which could be explained as visual perception of intramuscular fat content, was not significantly different between production seasons, therefore it is assumed that the fatty acid composition could have a more important role as shown by Pleadin et al (2015).Aroma and flavor are key attributes that have an impact on the overall acceptance of dry-cured products(Górska et al, 2017). Results in the present studyrevealed that butter flavor differed significantly (P<0.05) between production seasons.…”
supporting
confidence: 57%
“…Namely, Buscailhon et al (1994) reported that tenderness decreases with ageing of the hams. Monin et al (1997) that produce a wide range of volatiles and precursors (Toldrá and Flores, 1998;Toldrá, 2009;Górska et al, 2017). According to Gonzalez and Ockerman (2000) and Gandemer (2002) processing duration and temperature have a major impact on the course of lipolysis and proteolysis, the content of free amino and fatty acids, and the activity of lipolytic and proteolytic enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, high levels of hexanal were detected in other cold meats, for example dry fermented sausages [Bruna et al, 2001]. The aroma of hexanal is perceived as unpleasant, rancid, nauseating, hot, similar to aroma of green leaves, vegetables, or grass [Górska et al, 2016]. It can be deduced that this compound had an impact on the aroma of the studied półgęsek.…”
Section: Volatile Compounds Profi Le Of Półgęsekmentioning
confidence: 93%
“…The smoked bacon stored for 30 days (SB30) had the highest intensity of salty taste. This taste is not only related to the amount of salt added to the product, but is also influenced by the amount of intramuscular fat, nucleotide and amino acid compounds (Górska, Nowicka, Jaworska, Przybylski, & Tambor, 2017). It was probably related with the high glutamic acid content in this sample (Table 2).…”
Section: Overall Liking and Rate-all-that-applymentioning
confidence: 85%